PEMBINAAN MASYARAKAT DESA SIMPANG PETAI MELALUI PEMBERDAYAAN SANITASI LINGKUNGAN: sanitasi lingkungan - Wulandari, Cahya; Riska, Eka; Malaika, Shera; Krisdayanti; Rahayu, Tasya; Agustin, Marsya (IKATAN ALUMNI DOSEN MAGANG KEMENRISTEKDIKTI TAHUN ANGKATAN 2017, 2024)
The development of an area usually begins with improving public health. With healthy conditions, people will be able to carry out all activities well. The aim of this activity is to improve environmental sanitation and health in the Simpang Petai village community. With better sanitation and environmental health conditions, it is hoped that the community development program will be achieved. To find out the efforts of the government and local communities in dealing with sanitation problems in their environment. Community empowerment through environmental sanitation programs can involve education, active participation in waste management, and the construction of environmentally friendly sanitation facilities.